2019
DOI: 10.1176/appi.ajp.2018.18070881
|View full text |Cite
|
Sign up to set email alerts
|

No Support for Historical Candidate Gene or Candidate Gene-by-Interaction Hypotheses for Major Depression Across Multiple Large Samples

Abstract: Interest in candidate gene and candidate geneby-environment interaction hypotheses regarding major depressive disorder remains strong despite controversy surrounding the validity of previous findings. In response to this controversy, the present investigation empirically identified 18 candidate genes for depression that have been studied 10 or more times and examined evidence for their relevance to depression phenotypes.Methods: Utilizing data from large population-based and case-control samples (Ns ranging fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
380
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 551 publications
(400 citation statements)
references
References 60 publications
12
380
0
8
Order By: Relevance
“…We have therefore focused on the DTC scenario because errors in raw SNP-chip data could cause significant harm to patients without further validation. However, erroneous results from SNP-chips used in research biobanks can also lead to false associations [32] and wasted resource in the development of new treatments against the wrong targets [33].…”
Section: Discussionmentioning
confidence: 99%
“…We have therefore focused on the DTC scenario because errors in raw SNP-chip data could cause significant harm to patients without further validation. However, erroneous results from SNP-chips used in research biobanks can also lead to false associations [32] and wasted resource in the development of new treatments against the wrong targets [33].…”
Section: Discussionmentioning
confidence: 99%
“…From an historical perspective, the structure of mental health assessments developed from the belief that psychiatric conditions are predominantly biological and genetic (Stiffler & Dever ). This has proven not to be the case (Border et al, ; Borsboom et al, ; Torrey & Yolken ). A report on mental health and well‐being from the United Nations Special Rapporteur confirmed that many concepts associated with the biomedical model in mental health have failed to be supported by research.…”
Section: Discussionmentioning
confidence: 98%
“…However, the only outcome measure in our study which partially captures depressive symptoms is AYMH, which has been noted to have only moderate sensitivity in girls and poor sensitivity in boys . In addition, a recent study by Border et al (2019) with over 115,00 participants assayed these genes as well as all variants commonly tested for association with depression (i.e. tested in more than 10 studies) and found no associations between genetic variation and any depressive phenotypes.…”
Section: Discussionmentioning
confidence: 99%